(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The problem of mortality from cardiovascular diseases continues to be relevant throughout the world. At the same time, SCD accounts for about half of all deaths. The implementation of the SCD scenario occurs as a result of the development of acute left ventricular failure against the background of malignant ventricular arrhythmias, the manifestation of which is accompanied by disturbances of both systemic and regional hemodynamics, primarily from the central nervous system. The presence or absence of structural pathology of the heart may be of decisive importance for adaptive changes in cardiac output parameters, and therefore for the nature of the clinical course of arrhythmia. In this regard, the key significance for the clinical interpretation of the malignant course of any arrhythmia and determination of its life-threatening nature should be considered: fainting, presyncope, dizziness, hypotension, progression of manifestations of heart failure, angina pectoris.